Confinamento clássico e quântico de partículas induzido pela geometria - Formiga, Jansen Brasileiro (2011)
Since many models in physics depend on the confinement of particles in certain regions of the space-time, like Rubakov and Randall-Sundrum models, we analyze the possibility of using geometrical fields to confine particles. In doing so, we exhibit some examples of the confinement of particles by using only geometrical fields such as torsion and Weyl 1- form. In order to prepare the reader to these examples, we give a brief introduction to the Riemannian and the non-Riemannian geometries. It turned out to be impossible to avoid controversial issues such as the equation of motion of a particle, the use of the minimal coupling procedure, and the application of the variational principle for non-Riemannian geometries. However, we avoided choosing what approach was right and decided to take two completely different approaches into account, namely, Kleinert's and Hehl's ones. Kleinert claims that particles must follow autoparallel, while Hehl and others state that the equation of motion of a particle must be derived from a conservation law related to the energy-momentum tensor of the particle. As a matter of fact, there are more differences between those approaches than we have mentioned here, but we expect this thesis to clarify those differences. To be more precise, we managed to exhibit examples of confinement only for Kleinert's approach. We had dificulty finding a example of confinement to hehl's approach, however we were able to eliminate the possibility of confinement for many cases, like scale fields for example.